Patients with dementia: prevalence and type of drug–drug interactions - Muñoz-Contreras, María Cristina; Cerdá, Begoña; López-Román, Francisco Javier; Segarra, Ignacio (Frontiers in Pharmacology, 2024)
Background: Patients with Alzheimer's disease (AD) and other dementias are more frequently exposed to polymedication, mainly due to the presence of comorbidities, are particularly vulnerable to drug-related problems and present greater risk of adverse effects due to drug-drug interactions (DDI). Purpose: To assess the prevalence of clinically relevant interactions in dementia patients using a routine database; describe the most frequent interactions and risk factors associated with them to facilitate specific interventions and programs to prevent and minimize them. Methods: An observational, descriptive, cross-sectional, AD and other types of dementia patients (n=100, 64% female) study was conducted to identify potential DDI in their treatment using the Lexi-Interact/Lexicomp ® database. Results: A total of 769 drugs were prescribed, involving 190 different active ingredients, 83% of the treatments included 5 or more drugs. DDI occurred in 87% of the patients of which 63.2% were female. A total of 689 DDIs were found, grouped in 448 drug pairs, with a mean of 6.9±7.1 (range 0-31) DDIs per patient, and 680 DDIs were considered clinically relevant. It was observed that 89.8% of the DDIs had a moderate level of severity, 23.5% a good level of relevance and pharmacodynamic-based DDI accounted for 89.5% of the interactions. The drugs most frequently involved in DDIs were quetiapine (24.5%) and acetylsalicylic acid (10%). A total of 97 DDIs were detected between the AChEI and the rest of the drugs administered concomitantly. One of the most frequent DDI was between AChEI and beta-blocking agents, n=29, 4.3%. The most important factors that showed the strongest association with the presence of drug interactions were the use of AChEI (p=0.01) and the total number of drugs (p=0.014) taken by the patient. Conclusions: Patients with dementia present increased risk of DDI. Among the most common drugs are psychotropic drugs, which are involved in pharmacodynamic interactions caused by the concomitant use of CNS targeted drugs. The results highlight the difficulty to evaluate DDIs in clinical practice due to polymedication and variety of comorbidities. Therefore, it is important to review their treatment and consider metabolism inhibition or induction and potentially P450 substrate overlapping.